Pengaruh Profitabilitas dan Likuiditas terhadap Keputusan Stock Split dengan Mediasi Tingkat Kemahalan Harga (Jurnal Simki Economic, 2024)
Since semester 2 of 2020, when COVID-19 began to be handled well, world economic developments began to show positive growth. In 2021, world economic growth is 5.9% and Indonesia's economic growth is 3.7%, it is estimated that world economic growth in 2022 will be at 4.5% and Indonesia at 5.1%. This also has an impact on the movement of world stock exchanges and also the Indonesian stock market. ICI was at 5,900 at the end of 2020, at the end of 2021 it reached 6,500 and even reached 7,200 at the end of April 2022. This shows that the Indonesian capital market is very attractive to investors. One of the biggest banks in Indonesia, PT Bank Central Asia Tbk, has a market capitalization of Rp. 930 T in 2021, making it a very appealing investment. However, the share price of this bank is only IDR 36,600. With the high level of stock prices acting as a mediator, the goal of this study is to ascertain the impact of profitability and liquidity on stock split decisions. This study uses secondary data from 2014 to 2022 Q1 financial statements. This research uses SEM analysis technique using SmartPLS. As a result, profitability has a significant positive effect on stock split decisions through the mediation of price expensiveness levels and liquidity has a significant negative effect on stock split decisions through mediation of price expensiveness levels.